Metformin-NSAIDs Molecular Salts: A Path towards Enhanced Oral Bioavailability and Stability - Francisco Javier Acebedo-Martínez; Alicia Domínguez-Martín; Carolina Alarcón-Payer; Carolina Garcés-Bastida; Cristóbal Verdugo-Escamilla; Jaime Gómez-Morales; Duane Choquesillo-Lazarte (MDPI AG, 2023)
According to the World Health Organization, more than 422 million people worldwide have diabetes. The most common oral treatment for type 2 diabetes is the drug metformin (MTF), which is usually formulated as a hydrochloride to achieve higher water solubility. However, this drug is also highly hygroscopic, thus showing stability problems. Another kind of worldwide prescribed drug is the non-steroidal anti-inflammatory drug (NSAID). These latter, on the contrary, show a low solubility profile; therefore, they must be administered at high doses, which increases the probability of secondary effects. In this work, novel drug-drug pharmaceutical solids combining MTF-NSAIDs have been synthesized in solution or by mechanochemical methods. The aim of this concomitant treatment is to improve the physicochemical properties of the parent active pharmaceutical ingredients. After a careful solid-state characterization along with solubility and stability studies, it can be concluded that the new molecular salt formulations enhance not only the stability of MTF but also the solubility of NSAIDs, thus giving promising results regarding the development of these novel pharmaceutical multicomponent solids.